2020
DOI: 10.7759/cureus.10700
|View full text |Cite
|
Sign up to set email alerts
|

Glimepiride and Metformin Combinations in Diabetes Comorbidities and Complications: Real-World Evidence

Abstract: Objective To evaluate the usage of various strengths of glimepiride and metformin fixed-dose combinations in the management of type 2 diabetes mellitus (T2DM) patients with comorbidities and complications. Methods A retrospective, non-randomized, non-comparative, multi-centric real-world study included T2DM patients (age > 18 years) taking glimepiride and metformin fixed-dose combinations. Age, duration of diabetes, diabetes complications, comorbidities (hypertension and dyslip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The early combination therapy with glimepiride and metformin is the most commonly used combination, whereas DPP-4 inhibition is the new approach of treatment for T2DM which has the potential to reduce and may even normalize both FPG and PPG concentrations without adverse effects such as weight gain and hypoglycemia. Few studies have reported conflicting results of both tenelipliptin and glimepiride added to metformin regarding the efficacy of antidiabetic agents and safety outcomes [12][13][14][15]. Among 90 patients participated in the study the age ranged between > 30 to <80 maximum were from adulthood (51-60) age group.…”
Section: Resultsmentioning
confidence: 99%
“…The early combination therapy with glimepiride and metformin is the most commonly used combination, whereas DPP-4 inhibition is the new approach of treatment for T2DM which has the potential to reduce and may even normalize both FPG and PPG concentrations without adverse effects such as weight gain and hypoglycemia. Few studies have reported conflicting results of both tenelipliptin and glimepiride added to metformin regarding the efficacy of antidiabetic agents and safety outcomes [12][13][14][15]. Among 90 patients participated in the study the age ranged between > 30 to <80 maximum were from adulthood (51-60) age group.…”
Section: Resultsmentioning
confidence: 99%
“…Glimemil has the characteristics of fast binding to receptors, short time of interaction with membrane receptors, and fast hypoglycemia [13]. It can also increase nonoxidative metabolism by increasing glucose transporters, thereby reducing blood sugar [14,15]. e results of this study showed that the post-treatment insulin resistance index (HOMA-IR), fasting blood glucose (FPG), 2 h postprandial blood glucose (2hBG), serum glycated hemoglobin (HbA1c), triglyceride (TG) in the study group and control group, total cholesterol (TC), serum malondialdehyde (MDA), ROS, VEGF, and TRACP-5b levels were significantly lower than those before treatment, and the degree of reduction in the study group was greater than that in the control group, glimepiride may improve insulin sensitivity, reduces insulin resistance, and has always reduced blood glucose and blood lipids in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another multicenter study conducted in India increased the achievement of glycemic goals and lipid levels without any severe adverse events [59]. Fixed-dose combinations of glimepiride + metformin have been effective in managing T2DM among newly diagnosed and long-standing diabetes patients [60] in India. Kim et al [61] noted significant improvement in the fasting plasma glucose and HbA1c levels with FDC of glimepiride metformin among T2DM patients inadequately managed by low-dose metformin monotherapy.…”
Section: Glimepiride + Metformin + Pioglitazone: a Budget-friendly Al...mentioning
confidence: 99%